(untitled) (Revista científica Olimpia, 2023)
Sport, with its characteristic of emotional and pleasurable involvement with different audiences, is constantly used in marketing that involves differentiation, approximation of specific customers and search for the development of fundamental values important for the competitive environment.Thus, this study aimed to analyze how sport was inserted in Higher Education Institutions in Mozambique and how it is used in marketing, through the case study of the Polytechnic University of Mozambique. It was decided to carry out the study in an exploratory way, with a qualitative analysis, in order to obtain more in-depth information on the subject.It was found that sport is a fundamental variable in organizational management much more than a simple communication channel. Initiated through partnerships with traditional clubs in the city of Maputo. Thus, the relationship with sport strengthens the brand in a social context and competitive advantages are obtained in the market, making the institution an example with regard to the union between sport and marketing.